2020
DOI: 10.1016/j.ijppaw.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Toxoplasma gondii from captive caracals (Caracal caracal)

Abstract: Toxoplasma gondii infects most warm-blooded animals, including humans. Felids can serve as both intermediate and definitive hosts for T. gondii . However, there is no direct evidence to prove the caracal ( Caracal caracal ) is an intermediate host for T. gondii . Here, we report T. gondii infection in two caracals in a zoo from China. Antibodies against T. gondii were found in both cara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This finding indicates that T. gondii oocysts contaminate the habitat of these monkeys. The high seropositivity and isolated viable of T. gondii in captive tigers, serval, caracals, white spoonbills and sheep from Central China support this hypothesis (Dong et al., 2019; Jiang et al., 2020a, 2020b; Yang et al., 2019, 2020). It should not be ignored that T. gondii tachyzoites were recovered from the bronchoalveolar lavages of T. gondii ‐inoculated squirrel monkeys and that T. gondii may be horizontally transmitted by aerosol between infected monkeys and cage mates (Furuta et al., 2001).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding indicates that T. gondii oocysts contaminate the habitat of these monkeys. The high seropositivity and isolated viable of T. gondii in captive tigers, serval, caracals, white spoonbills and sheep from Central China support this hypothesis (Dong et al., 2019; Jiang et al., 2020a, 2020b; Yang et al., 2019, 2020). It should not be ignored that T. gondii tachyzoites were recovered from the bronchoalveolar lavages of T. gondii ‐inoculated squirrel monkeys and that T. gondii may be horizontally transmitted by aerosol between infected monkeys and cage mates (Furuta et al., 2001).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have identified ToxoDB#9 ( Chinese 1 ), ToxoDB#2, ToxoDB#4, ToxoDB#20, ToxoDB#17, ToxoDB#292 T . gondii genotypes in animals from Central China, ToxoDB#9 and ToxoDB#2 were the predominant genotypes in China (Dong et al., 2019; Jiang et al., 2020a, Jiang et al., 2020b; Su et al., 2019; Yang et al., 2015, 2019). ToxoDB#3 and mixed infections were identified in a ring‐tailed lemur and a squirrel monkey from China (Huang et al., 2018; Yang et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…ToxoDB#2 (type III) is widely distributed worldwide, including Asia, Africa, South Europe, North America, South, and Central America ( Chaichan et al, 2017 ; Dubey, 2010 ; Dubey et al, 2013 , 2014 ; Shwab et al, 2018 ). ToxoDB#2 T. gondii strains have been found in cats ( Yang et al, 2015 ), lambs ( Jiang et al, 2020a ), caracal ( Jiang et al, 2020b ), white Spoonbill ( Yang et al, 2020 ), and kangaroo ( Yang et al, 2023 ) from central China, all of them were 3/3 for ROP18/ROP5 and most of them were avirulence for mice (except TgRooCHn3). They share the same genotype, and ROP18/ROP5 allele, this indicates that TgTigerCHn4 may be of local origin.…”
Section: Discussionmentioning
confidence: 99%
“…a ROP18/5 allele combination and CS3 profile are considered to have predictive value for the virulence in mice ( Pena et al., 2008 ; Shwab et al., 2016 ); isolates with low passage history ( Khan et al., 2014 ). b Morbidity scoring and humane endpoint ( Pena et al., 2021 ); tabulation of data ( Jiang et al., 2020 ); LD 50 calculations (Probit tests). c Virulence classification ( Su et al., 2002 ; Dubey et al., 2014 ; Saraf et al., 2017 ).…”
Section: Proposed Methodology For Virulence Assessment Of T...mentioning
confidence: 99%
“…Another useful way to measure parasite transmissibility is to evaluate parasite cystogenesis, the capacity and capability of T. gondii to form tissue cysts. The central nervous system (CNS) is the tissue par excellence to study the development of cysts during the chronic phase of the infection but the T. gondii tropism towards immune privileged organs also involves ocular or muscle tissues ( Jiang et al., 2020 ; Yang et al., 2020 ; Dubey, 2021 ). Cysts can be quantified and even measured (diameter) by microscopic observation of fresh/unstained ( Dubey et al., 2012 ) and immunostained fixed brain sections or brain homogenates ( Masatani et al., 2020 ; Wang and Sibley, 2020 ).…”
Section: Complementary Approaches On the Determination Of Virulence I...mentioning
confidence: 99%